Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan dan Loyalitas Pengguna MyTelkomsel Dengan Menggunakan Model E-Service Quality dan E-Recovery Service Quality (Studi Kasus : Pengguna Aplikasi MyTelkomsel Malang) - Fauzan Adi Laksono; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
MyTelkomsel is a self service application launched by Telkomsel that is useful for facilitating its customers. However, MyTelkomsel still gets complaints from users. These complaints are found in the Playstore review column and could be a failure of the login process, a failure of transaction process, and customer dissatisfaction about online customer service. This study aims to determine what factors in the service quality of MyTelkomsel that can affect customer satisfaction and user loyalty of MyTelkomsel in Malang. The models used in this study are E-Service Quality and E-Recovery Service Quality. This study used a sample of 102 respondents that used MyTelkomsel application and are domiciled in Malang. The sampling technique used in this study was purposive sampling. Data was collected by distributing questionnaires directly to respondents in the Grapari Telkomsel Malang office. Data analysis used in this study are multiple linear regression and simple linear regression models. From this research, it was found that the efficiency and privacy variables had a significant effect partially on customer satisfaction and customer satisfaction had a significant effect partially on user loyalty.